KOMBINASI CONTRACT RELAX STRETCHING DAN INFRA MERAH SAMA BAIKNYA DENGAN PEDAL EXERCISE UNDERCOMPRESSION DAN INFRA MERAH UNTUK MENURUNKAN NYERI OTOT BETIS PADA PEMBATIK CAP DI BUARAN PEKALONGAN - Wulandari, Irine Dwitasari; Adiputra, Nyoman; -, Sugijanto (Sport and Fitness Journal; Volume 3, No.3, 2015, 2015)
The work attitude ofstampbatik workers in conductedtheir dailyworkin standing position. Stands work attitudeina longtimewillmake theworkeralwaystryingto balance the body thus causing the static load on the feet. Static muscle contraction in along time will cause ashort age of muscle blood flow, which results in reduced energy exchange and egress metabolic wastein the active muscles, thus causing fatigue and pain. The processing volvesa lot of loading on static muscle is faster cause muscle complaints, and this affects of the ability and decrease in labor productivity result. The purposefor knowing whether combination of contract relax stretching and infrared are better to decrease calf muscle pain compared with pedal exercise under compression and infrared on the stamp batik workerin home industries Buaran Pekalongan. Types of experimental research, with the randomized study design pre and post test control group design. Group-1 (n =14) subjectswho receivedpedal exercise under compressionandinfrared, whileGroup-2 (n=14) get contract relax stretching and infrared. Analysis ofthe datawith thePaired Sample t-Test design mean scoresin the calf muscle pain in group 1beforetreatmentwas142,857 mmHg and after 6 times treatment be172,142 mmHg, p =0.000. While the scores of calf muscle pain in Group-2 before treatment was 142,857 mmHg and after 6 times treatment be170,714 mmHg, p =0.000. Different testgroupswithGroup1 and Group 2 with astatistical analysis of Independent Sample-t Test value of p=0,871 (p>0.05).The conclusions obtained were exercise programs ofcontract relax stretchingand infrared with pedal exercise under compression and infra red together can decrease calf muscle pain on the stamp batik worker. There is no significant different between the turn combination of contract relax stretching and infrared with pedal exercise under compression and infraredto decrease calf muscle pain on the stamp batik worker.
Keywords: contract relaxstretching, pedal exercise under compression, infra-red, calf muscles pain, stamp batik workers